Influence of Rhizobacteria on Soil Ion Concentration under Paddy Cultivation - Elmi Junita Tarigan; Cahyo Prayogo; Yu-Ting Weng; Chesly Kit Kobua; Ying-Tzy Jou; Yu-Min Wang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Sustainable agriculture requires nutrient management options that can increase crop yields that are profitable for N nutrient availability and are environmentally friendly. However, N nutrient is dynamic and easy to lose, and excessive use of chemical N fertilizers has a negative impact on the environment. Biofertilizer by rhizobacteria is an effective way to maintain a reliable N-supply for rice growth. This study investigates the effect of a different combination of rhizobacterial fertilizers on nitrogen ion concentration in the soil and total rice production. The field experiment was conducted in two seasons. There were three treatments, including PGPR with 25% CF, PGPR with 50% CF, and 100% CF. The soil sample was taken from each treatment in six growth stages of rice i.e. 15, 36, 50, 72, 100, and 118 days after transplanting. Soil chemicals NH4+ and NO3- were analyzed by Ion Chromatography. The results showed that the uniformity of NH4+ and NO3- in the soil were the highest in fertilizer application with PGPR. The application of PGPR with 50% CF confirms that it can increase rice yields by 25.5% and 12.9%, respectively. The application of rhizobacteria can reduce the use of chemical fertilizers.